Nose vs. mouth breathing- acute effect of different breathing regimens on muscular endurance - František Lörinczi; Marián Vanderka; Drahomíra Lörincziová; Mehdi Kushkestani (BMC, 2024)
Abstract Background It has been reported that the way we breathe (whether through the nose or mouth) can influence many aspects of our health and to some extent, sport performance. The purpose of this study was to evaluate the acute effects of different breathing regimens on muscular endurance and physiological variables. Methods A randomized experiment to verify the acute effect of different breathing regimens (NN- inhaling and exhaling through the nose; NM- inhaling through the nose, exhaling through the mouth; MM- inhaling and exhaling through the mouth) on the muscular endurance performance was conducted. 107 physically active college students (68 males, 39 females) performed repeated bench press testing protocol (repetitions to failure (RTF) with 60% of body weight for males (BP60), respectively 40% of body weight for females (BP40)) with various breathing regimens (NN, NM, MM) in random order. Heart rate (HR), blood oxygen saturation (SpO2) and perceived exertion by Borg scale (RPE) were measured as well. A short questionnaire, given after the testing protocol and observation during familiarization, was used to detect each subject's normal breathing approach during resistance training. Results In both genders, no significant differences in RTF, RPE and SpO2 were found. No individual case of deviation of arterial oxygen saturation outside the physiological norm was recorded. ​​In the male group, significantly lower HR values were found during the NN trials, compared to during the NM (p = 0.033) and MM (p = 0.047) trials with no significant differences in females. The HR differences in the males demonstrated a small effect size (NN < NM, d = 0.32; NN < MM, d = 0.30). Questionnaire results suggest that 80% of our participants use NM breathing, 15% use MM breathing and 5% use NN breathing during resistance training. Conclusion It seems, that various breathing regimens have none or only minor effect on muscular endurance performance and selected physiological parameters. NN seems to be as efficient as other two regimens, which are mostly used in practice (NM, MM).